Exploring the trait plasticity of ipa1-2d and qpl6 under different nitrogen treatments and heading periods - Zhuang, Wenshu; Jin, Guangyang; Zou, Yiting; Bian, Zhong; Xie, Dong; Zhang, Shuwei; Yeilaghi, Hadi; Yu, Liangliang; Wong, Muiyun; Fan, Xiaolei; Zhao, Dongsheng; Liu, Qiaoquan; et al. (Tech Science Press, 2024)
Panicle size is one of the important factors in shaping yield potential in rice, but it shows plasticity in different environments, which leads to yield fluctuation. Variations in panicle size among varieties are largely determined by quantitative trait loci (QTLs). QTL analysis could elaborate on the environmental impact on trait plasticity using nearly isogenic lines (NILs) of different QTLs. Two QTLs, ipa1-2D and qPL6 are identified to have pleio-tropic contributions to panicle size and plant architecture, but their responses to different growth conditions are still unclear. In this study, we developed NILs harboring a single locus or both loci of ipa1-2D and qPL6 and sub-sequently evaluated these QTL effects under different nitrogen treatments or heading periods. Trait comparison showed that panicle length was highly responsive to the high nitrogen treatment independent of qPL6. At the same time, ipa1-2D reduced the response of plant height, panicle number, and grain yield to the treatment. The background of long heading periods decreased the stem diameter for any genotype combinations but enhanced the performance of ipa1-2D for the panicle primary branch number. Moreover, the middle heading background could better balance the pleiotropic effect of the two QTLs and showed the highest yield potential. In-parallel analysis of the QTL contributions under different nitrogen treatments or heading periods confirmed the significant effect of ipa1-2D in increasing stem diameter, panicle primary branch number, and spikelet number per panicle. We proved that the two individual QTLs had a stable effect in increasing the yield potential but com-peted to decrease the panicle secondary branch number, panicle number, and yield potential when they were pyr-amided. This work provides a full view of the plasticity of two QTLs in shaping yield-related traits and lays the foundation for the rational design of rice breeding in the future.